Implementasi pendidikan antikorupsi pada mata pelajaran PPKn berbasis project citizen di sekolah menengah atas - Sutrisno Asyafiq (Jurnal Civics: Media Kajian Kewarganegaraan)
This research was aimed at describing the implementation of anti-corruption education on citizenship education through project citizen-based activity. It is descriptive inquiry conducted at SMA Muhammadiyah 1 Ponorogo. The result was that the implementation of  anti-corruption education was conducted through studying problems relating corruption resulting in presentation panels consist of 4 sections namely problem, alternative policy, proposed solution, and action plan section. Through these activities, it was intended that students would acquired some desired attitudes such as honesty, care, self-help, discipline, responsibility, hard work, humbleness, courage and justice.